Short-Term Quality of Life After Myomectomy for Uterine Fibroids From the Compare-UF Fibroid Registry. Issue 5 (May 2020) - Laughlin-Tommaso, Shannon K.; Lu, Di; Thomas, Laine; Diamond, Michael; Wallace, Kedra; Wegienka, Ganesa; Vines, Anissa; Anchan, Ray; Wang, Tracy; Maxwell, G. Larry; Jacoby, Vanessa; Marsh, Erica E.; et al.
Abstract : (Abstracted from Am J Obstet Gynecol 2020;222:345.e1–345.e22) Uterine fibroids can have a substantial impact on quality of life of reproductive aged women and are a leading cause of morbidity and surgery in affected women. A uterine-sparing treatment option for patients with symptomatic uterine fibroids is myomectomy.